PQM130, a Novel Feruloyl–Donepezil Hybrid Compound, Effectively Ameliorates the Cognitive Impairments and Pathology in a Mouse Model of Alzheimer’s Disease - Morroni, Fabiana; Sita, Giulia; Graziosi, Agnese; Ravegnini, Gloria; Molteni, Raffaella; Paladini, Maria Serena; Dias, Kris Simone Tranches; dos Santos, Ariele Faria; Viegas, Claudio; Camps, Ihosvany; Pruccoli, Letizia; Tarozzi, Andrea; et al. (Frontiers in Pharmacology, 2019)
Alzheimer's disease (AD) is the most common neurodegenerative disease in older people. The multifactorial nature of AD calls for the development of multitarget agents addressing key pathogenic processes. Donepezil, an acetylcholinesterase inhibitor, is a first-line acetylcholinesterase inhibitor used for the treatment of AD. Although extensive studies have demonstrated the symptomatic efficacy of donepezil treatment in patients with AD, the effects of donepezil, if any, on the AD process are not known. In the present study, a novel feruloyl-donepezil hybrid compound (PQM130) was synthesized and evaluated as multitarget drug candidate against the neurotoxicity of Aβ1-42 oligomers (AβO) in mice. PQM130 had already shown anti-inflammatory activity in the mice paw edema, pleurisy and formalin-induced hyperalgesy models, in vitro metal chelator activity for Cu2+ and Fe2+, and neuroprotection of human neuronal cells against oxidative damage. An intracerebroventricular (i.c.v.) injection of AβO into the mouse brain triggered increased reactive oxygen species levels, neurodegeneration, neuroinflammation, and memory impairment. In contrast, the intraperitoneal administration of PQM130 (0.5-1 mg/kg) after i.c.v. AβO-injection counteracted oxidative stress, induced cell survival and protein synthesis through the modulation of glycogen synthase kinase 3β (GSK3β) and extracellular signal–regulated kinases (ERK1/2) and the increased brain derived neurotrophic factor (BDNF) and synaptophysin levels in the hippocampus of mice. Additionally, PQM130 treatment decreased AβO-induced neuronal apoptosis, via caspase pathway, and neuroinflammation. Moreover PQM130 improved learning and memory, protecting mice against the decline in spatial cognition. Even more interesting is that PQM130 modulated different pathways compared to donepezil and it is much more effective in counteracting AβO damage. Therefore, our findings highlighted that PQM130 is a potent multi-functional agent against AD and could act as promising neuroprotective compound for anti-AD drug development.